Effect of the heme oxygenase gene on mycelial growth and polysaccharide synthesis in Ganoderma lucidum. (5th February 2021) - Wang, Ting; Wang, Yihong; Chen, Chen; Ren, Ang; Yu, Hanshou; Zhao, Mingwen
Abstract: The heme oxygenase gene has antioxidant and cytoprotective effects in organisms, but no related research has been conducted in Ganoderma lucidum . For the first time, we cloned the HMX1 gene in G. lucidum . The CDS is 1092 bp in length and encodes 363 amino acids. The HMX1 protein was prokaryotically expressed and purified, and the enzyme activity of the purified protein was measured. The value of K m was 0.699 μM, and V m was 81.9 nmol BV h −1  nmol −1 protein. By constructing the silencing vector pAN7‐dual‐HMX1i, the transformants HMX1i1 and HMX1i2 were obtained. Compared with the wild‐type (WT), the average growth rate of HMX1i1 and HMX1i2 decreased by 31% and 23%, respectively, and the mycelium biomass decreased by 53% and 48%, respectively. Compared with the WT, the extracellular polysaccharide content of HMX1i1 and HMX1i2 increased by 59% and 51%, and the intracellular polysaccharide content increased by 24% and 22%, respectively. These results indicate that the HMX1 gene affects mycelial growth and polysaccharide synthesis in G. lucidum .